Geomechanical Response of Buner Marble, Pakistan, to Elevated Temperatures: Triaxial Strength Analysis through Single and Multistage Approaches (Rudarsko-geološko-naftni zbornik, 2025)
This study investigates the effect of three-dimensional stress on the strength of marble from the Buner District, Khyber Pakhtunkhwa. It provides a comparative analysis of single and multi-stage triaxial tests to evaluate marble strength under ambient and elevated temperatures. Additionally, this study examines the physico-mechanical properties of the selected marble to enhance the understanding of its performance under varying conditions. A total of five bulk marble samples, (BM1 to BM5) were collected. From these samples, seventy (70) cores were extracted for the investigation of various physico-mechanical properties. Physical tests, including specific gravity, porosity, water absorption, and ultrasonic pulse velocity (UPV), as well as mechanical tests, such as unconfined compressive strength (UCS), unconfined tensile strength (UTS), point load test (PLT), and triaxial testing, were conducted. Physical properties were determined for five specimens (BM1 to BM5) selected from the bulk sample, while mechanical tests were carried out on the remaining 65 samples. Overall significant uniformity was observed in the values of all physico-mechanical properties except water absorption, which was found relatively higher in the case of BM3 and BM5 (0.093%) due to the increased amount of hydrophilic minerals in these samples. The remaining core specimens were treated at elevated temperatures (50°C, 75°C, 100°C, and 150°C). The mechanical properties including UCS, UTS, PLT, and triaxial tests were obtained on samples at ambient (25°C) and elevated temperatures. In the case of UCS and UTS, it was found that strength increases with an increasing temperature to a threshold temperature of 100°C, followed by a decrease at 150°C. Similarly, for the strength parameters (cohesion and friction angle) obtained during the triaxial tests, the threshold temperature was again found to be 100°C, thereafter strength degradation of the rocks occurred. The increase in strength is attributed to mineral thermal reactions causing the new bonding agents leading to the strengthening of rocks. Whereas, the decrease from 100°C to 150°C occurred due to the mineral thermal expansion resulting in thermal cracking and reduced strength. Based on the derived results, analysis, and their comparison with international standards, the studied rocks can be used for various underground construction purposes.